Analisis Penggunaan Ornamen Pada Desain Poster - Muhammad Fikri Haikal; Satriadi Satriadi (Nuansa Journal of Arts and Design, 2023)
Posters are one of the visual communication media used to convey messages or information to the audience. This study aims to identify ornaments in poster design from the perspective of audience aesthetics by considering cultural developments in the Eastern hemisphere, namely China, the Middle East (Islam), and India. This study uses a literature review as a method to analyze poster designs focusing on ornamental needs in the design. The Interpretive Iconology ("thematic") approach is used to explain the meaning contained in these ornaments. The results of this study are expected to provide insight into how ornaments from these cultures can improve the effectiveness of visual message communication in poster designs targeted at audiences from diverse cultures.